Digital Transformation Readiness in Archival Management at a State Islamic Senior High School: Infrastructure, Competency, and Institutional Policy - Fasichah; Erica Wahyu Izzati; Lilik Huriyah (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Systematic records management is a fundamental infrastructure for accountable governance in educational institutions. Yet many Madrasah (Islamic schools) continue to face a substantial gap between the demands of digital transformation and their actual archival conditions. This study evaluates the digital transformation readiness of archival management at Madrasah Aliyah Negeri (MAN) a state Islamic senior high school in Surabaya City across three dimensions: technological infrastructure, human resource competency, and institutional policy. A qualitative-descriptive approach was employed; data were collected through an in-depth interview with one key informant the Head of Administration and direct observation of the archive room and operational systems. The evaluation was grounded in the records life cycle and records continuum model as analytical frameworks. The findings reveal that the institution has effectively utilized the SRIKANDI application (the Indonesian government's Electronic Correspondence and Archival Management System) and electronic signatures for digital correspondence, and has prepared storage infrastructure including a server and external hard drive. Nevertheless, three critical gaps were identified: a system dualism between digital and uncodified physical archives, the absence of professional archivists at the institutional level, and the lack of formal written archival policies. These findings indicate that the institution's digital transformation readiness is asymmetric infrastructure development has outpaced human capacity building and policy formulation